Home Museums are a Small Mirror of History - Shokhista Ablakulovna , Elmuratova (International Journal of Psychosocial Rehabilitation, 2020)
Country and its history and culture Preserving, researching, and using their treasures is every bit the duty of man. This is a great guide for historians to serve as a tool to preserve cultural heritage. Home museums were also established. This article is informative in character.